Pendekatan Positive Deviance Dalam Mereduksi Kejadian Malaria Di Kota Jayapura - Lisda Oktavia Madu Pamangin; Muhammad Akbar Nurdin; Fajrin Violita (The Community Engagement Journal, 2023)
Malaria is still a public health problem in the world, including in Indonesia. Positive deviation behavior is one of the factors that influence the incidence of malaria. So this study aims to determine the effect of positive deviation on the incidence of malaria in Jayapura City. This community service was carried out in the Mandala Village area, Jayapura City, Papua Province. The community service method uses the Community Empowerment method using Focus Group Discussion (FGD). Sampling using Exautive sampling (sampling technique when all members of the population are used as samples). The data collected will be analyzed using SPSS version 21.0. The results of the quantitative analysis showed that the most influential factor on the incidence of malaria was positive deviation (p=0.000). The results of the qualitative analysis show that positive deviation behaviors to prevent malaria are using mosquito nets when sleeping, wearing long sleeves when working and when going out at night, and burning trash and coconut belts. The positive deviation approach can be used as an effort to prevent and control malaria through the active role of health cadres or community leaders. Keywords: Malaria, Positive Deviance, Behavior, Prevention